Study Of Critical Flow Rate As A Water Coning Indicator In “Volve” Wells In Norway Production Fields - Dharma Arung Laby; Abdi Suprayitno; Amiruddin; Aprilno Alfa Kumasela; Abdul Gafar Karim; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Oil wells with water drive propulsion, if produced then water will move towards the well hole to form a cone. Under certain conditions, water will break into the well and begin to be produced along with oil and this phenomenon is called water coning, therefore a critical flow rate calculation is carried out to determine the limit of the flow rate allowed by the well to produce without water coning. The purpose of this final project research is to determine the value of the critical flow rate in the methods used, namely the Mayer Gardner and Pirson method and also the Schols method, and the calculation of time to brekthrought with the Sobicinski and Cornelius method is carried out to determine the time needed for water to reach bottom perforation. The results of calculating the flow rate with the Mayer Gardner and Pirson method of 5.21 STB / day, then obtained time to breakthrough for 82437,02 days, and at the flow rate with the schools method of 0.23 STB / day obtained a flow rate of 4729678 days and if the well is produced at the actual rate of 86.5684 STB / day then the time to breakthrough is obtained for 418 days.